Modern system of professional training of foreign language teachers - Безлюдна, В. В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The author examines the modern state of foreign language teacher training in higher educational institutions of Ukraine based on an analysis of university reports and curricula in the field of “Philology (language and literature (English))”. The main components of the system are educational and organizational work, use of innovative technologies, organization of pedagogical practice, organization of individual student work, distance education, monitoring of students’ progress. The analysis of the curriculum and modular principle of foreign languages teachers training allows the author to structure student training in blocks and arrange the discrete-continuous study of educational material with a full management cycle.It is established that the modern system of training foreign language teachers?? is characterized by unification and standardization of curricula and programs, increasing hours for individual work, use of various innovative, interactive, multimedia technologies. The author’s attention is focused on organization of pedagogical practice for foreign language teacher training in secondary school. Its essence lies in the fact that this practice being organized by a university and a secondary school is planned in close co-operation of teachers, psychologists, methodologists based on a common understanding of the idea of competence approach as a modern methodology of foreign language education. All these components create the most favourable conditions for the professional development of students, providing training that meets the growing demands on the modern teacher, his or her professional and personal qualities.